Silat Warriors, Heroism and Resistance: Tales from the Malay Archipelago (KEMANUSIAAN The Asian Journal of Humanities, 2026)
This article examines the notion of heroism in the Malay Archipelago and highlights the significance of Silat, the traditional Malay martial art, as a physical and spiritual discipline that shapes cultural identity and resistance to colonial subjugation. The research examines five notable Malay figures—Mat Salleh, Mat Kilau, Tok Janggut, Dato’ Maharaja Lela and Dol Said—who arose during colonial expansion and socio-political turmoil in Malaya. This study focuses on these figures due to their prominence in colonial-era resistance narratives. These individuals, celebrated for their expertise in Silat, illustrate the dichotomy of the warrior as both a protector of physical autonomy and a custodian of spiritual and ethical principles. Their opposition to colonial forces was sometimes described as a jihad (struggle) to safeguard Malay and Islamic traditions. The article analyses the mythologisation of these heroes in Malay folklore and national narratives, thereby converting them into lasting symbols of Malay identity. The article examines the relationship between Silat, heroism and resistance, providing an insight into the enduring impact of these historical figures on Malaysia’s cultural heritage and national memory, while challenging the reductionist interpretations of their intricate legacies in modern discussions.